SYTUACJA SPOŁECZNA ORAZ PRAWNA OCHRONA OSÓB STARSZYCH - Maj, Elżbieta (Wydział Prawa i Administracji UAM, 2012)
Artykuł stanowi próbę spojrzenia na problematykę starości przede wszystkim od strony aktywności legislacyjnej podejmowanej w ramach prawa krajowego w tym obszarze. Poza analizą obowiązującego obecnie system instytucjonalnego wsparcia osób starszych, w tym starszych osób niepełnosprawnych, wskazano na doniosłość owej problematyki w kontekście sytuacji demograficznej w Polsce i na świecie. Zwrócono uwagę na brak jednolitości i spójności w definiowaniu starości, a także na bariery ograniczające populację seniorów oraz ich społeczną marginalizację. Na podstawie wybranych aktów prawnych wykazano, że sytuacja osób starszych (w tym niepełnosprawnych) nie przedstawia się korzystnie, mimo że prawa osób starszych są raczej dobrze chronione.

*The paper is an attempt to look at the problems of the old age, mainly from the perspective of the legislative activity undertaken within the framework of relevant national law. Apart from the analysis of the current system of institutional support for elderly citizens and old people with disabilities, the importance of these issues in the context of the demographic situation in Poland and worldwide has been emphasised. Attention has been drawn to the lack of uniformity and cohesion in the definition of old age, and to the barriers that affect the population of seniors as well as social marginalisation of the elderly citizens. On the basis of selected legal acts it has been shown that the situation of the elderly (including the disabled) is far from favourable, although the rights of old people are relatively well protected.
LEGAL PROTECTION OF THE ELDERLY
Keywords: starość; osoba starsza; ochrona prawna; prawo; niepełnosprawność; old age; the elderly; law; disability